Metalibrarians as Residents Beyond the Second Life: An Overview of Contradictory Concept on “The Metaverse” - Sağsan, Mustafa (Information World, 2024)
The purpose of this paper is to understand the role of metaverse in libraries and librarians. The new conceptions; such as virtual reality, augmented reality, second life, metaverse, metamodernism, metaliteracy, and metalibrarian, have been discussed in the context of real-world libraries and librarians in the article. The organization of the article has been divided into four sections, which are interconnected with libraries and librarians. The first section starts with virtual reality (VR) and augmented reality (AR) technologies and underlines the important roles of the library and librarians. The second section continues the Second Life (SL), which is the pre-period of metaverse, and points out the importance of librarians and libraries. Finally, the fourth and last section focuses on the metaverse, as it is a new contradictory concept in the digital age, and discusses the metamodernism within the metaverse age by providing new roles and tasks for both libraries and librarians, which will be called “metalibrarian” thereafter. A systematic literature review has been used to position the role of metalibrarians among the other target groups such as educators, communicators, designers, et al. at the metamodernism age. As the existing literature indicates that metalibrarians have heavy duties on their shoulders to both design curricula for the metalibrary users, and manage information resources. Research has been proposed on the new roles, tasks, responsibilities, and competencies for metalibrarians to embrace the metaverse environment.